Caracterização de superfícies de titânio modificado por oxidação à plasma - Silva, Marco Aurélio Medeiros da (2013)
Recent years have seen a significant growth in surface modifications in titanium implants, resulting in shorter healing times in regions with low bone density. Among the different techniques, subtraction by chemical agents to increase oxidation has been applied for surface treatment of dental implants. However, this technique is generally unable to remove undesirable oxides, formed spontaneously during machining of titanium parts, raising costs due to additional decontamination stages. In order to solve this problem, the present study used plasma as an energy source to both remove these oxides and oxidize the titanium surface. In this respect, Ti disks were treated by hollow cathode discharge, using a variable DC power supply and vacuum system. Samples were previously submitted to a cleaning process using an atmosphere of Ar, H2 and a mixture of both, for 20 and 60 min. The most efficient cleaning condition was used for oxidation in a mixture of argon (60%) and oxygen (40%) until reaching a pressure of 2.2 mbar for 60 min at 500°C. Surfaces were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), atomic force microscopy (AFM), adhesion and cell proliferation. SEM showed less cell spreading and a larger number of projections orfilopodia in the treated samples compared to the control sample. AFM revealed surface defects in the treated samples, with varied geometry between peaks and valleys. Biological assays showed no significant difference in cell adhesion between treated surfaces and the control. With respect to cell proliferation, the treated surface exhibited improved performance when compared to the control sample. We concluded that the process was efficient in removing primary oxides as well as in oxidizing titanium surfaces